A 10-kDa class-CI sHsp protects E-coli from oxidative and high-temperature stress (PLANTA, 2003)
We report on a new cDNA clone (Qshsp10.4-CI) of a Quercus suber L. class-CI small heat-shock protein (sHsp) obtained from cork (phellem), a highly oxidatively stressed plant tissue. The deduced gene product lacks the C-terminal extension and the consensus I region of the alpha-crystallin domain, being the most C-terminally truncated sHsp reported to date. In an attempt to prove that a protective function is possible for such a truncated sHsp, we overexpressed in Escherichia coli three recombinant sHsp-CIs, one (rQsHsp10.4-CI) showing the same truncation as Qshsp10.4-CI, a second (rN49) lacking the whole alpha-crystallin domain, and a third (rN153) consisting of a full-length sHsp-CI. The overexpression of rN153 and, remarkably, rQsHsp10.4-CI but not rN49 enhanced cell viability under high temperature and, interestingly, under oxidative stress. These results show that the C-terminal extension and the consensus I region of the alpha-crystallin domain are dispensable, but amino acids 1-41 of the alpha-crystallin domain (including the consensus II region) are essential for the protective activity of sHsp-CIs. On the other hand, two-dimensional immunodetection patterns showed accumulation of ca. 10-kDa sHsp-CI immunorelated polypeptides in cork and other oxidatively stressed tissues but not in control and heat-stressed tissues. We discuss the possible role of highly truncated sHsps in relation to oxidative stress.